Digital Transformation and Financial Inclusion: Evidence from Rural Ranchi (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study explores the role of digital transformation in advancing financial inclusion among rural residents of Ranchi, Jharkhand. With the rapid expansion of digital financial services (DFS) such as UPI, mobile banking, and Aadhaar-enabled Payment Systems, rural populations are increasingly gaining access to formal financial systems. The research employs a quantitative approach, based on primary data collected from 123 respondents using a structured questionnaire. Descriptive statistics were used to analyse demographic factors, benefits, and barriers, while simple linear regression tested the causal relationship between usage of digital financial services and financial inclusion. The results show a significant and positive impact of digital financial services on financial inclusion, with regression analysis confirming that greater use of digital tools enhances access, reduces barriers, and improves overall participation in financial systems. Benefits such as convenience, time-saving, and easier access to government schemes were strongly acknowledged by respondents, while barriers such as poor internet connectivity and lack of digital literacy remain key challenges. The findings validate the hypothesis and indicate that digital financial tools can be powerful drivers of inclusion, provided infrastructural and awareness gaps are addressed. The study contributes to both academic literature and policy discourse by offering localized evidence on digital adoption in rural areas, thereby guiding targeted strategies to bridge the digital divide and promote inclusive economic growth.